PEKERJA SEKTOR INFORMAL DI KOTA AMBON - DEREK BAKARBESSY (Fakultas Ilmu Sosial dan Ilmu Politik, 2019)
This study aims to find out informal sector workers in Ambon city through case study. Determination of stratified random samples by first making the population classification according to certain characteristics and after that determined the number of samples with randomly selected system of 211 people, consisting of: people, seller drinks 109 people, fruit vendors 41, meatball seller 45 people. The data were analyzed quantitatively, in order to find out the utilization rate of labor force in the informal sector under study, the approach of the